Detailed Seismic Bathymetry Beneath Ekström Ice Shelf, Antarctica: Implications for Glacial History and Ice‐Ocean Interaction - Smith, Emma C.; Hattermann, Tore; Kuhn, Gerhard; Gaedicke, Christoph; Berger, Sophie; Drews, Reinhard; Ehlers, Todd A.; Franke, Dieter; Gromig, Rapahel; Hofstede, Coen; Lambrecht, Astrid; Läufer, Andreas; et al. (Geophysical Research Letters, 2020)
The shape of ice shelf cavities are a major source of uncertainty in understanding ice‐ocean interactions. This limits assessments of the response of the Antarctic ice sheets to climate change. Here we use vibroseis seismic reflection surveys to map the bathymetry beneath the Ekström Ice Shelf, Dronning Maud Land. The new bathymetry reveals an inland‐sloping trough, reaching depths of 1,100 m below sea level, near the current grounding line, which we attribute to erosion by palaeo‐ice streams. The trough does not cross‐cut the outer parts of the continental shelf. Conductivity‐temperature‐depth profiles within the ice shelf cavity reveal the presence of cold water at shallower depths and tidal mixing at the ice shelf margins. It is unknown if warm water can access the trough. The new bathymetry is thought to be representative of many ice shelves in Dronning Maud Land, which together regulate the ice loss from a substantial area of East Antarctica. Plain Language Summary: Antarctica is surrounded by floating ice shelves, which play a crucial role in regulating the flow of ice from the continent into the oceans. The ice shelves are susceptible to melting from warm ocean waters beneath them. In order to better understand the melting, knowledge of the shape and depth of the ocean cavity beneath ice shelves is crucial. In this study, we present new measurements of the sea floor depth beneath Ekström Ice Shelf in East Antarctica. The measurements reveal a much deeper sea floor than previously known. We discuss the implications of this for access of warm ocean waters, which can melt the base of the ice shelf and discuss how the observed sea floor features were formed by historical ice flow regimes. Although Ekström Ice Shelf is relatively small, the geometry described here is thought to be representative of the topography beneath many ice shelves in this region, which together regulate the ice loss from a substantial area of East Antarctica. Key Points: Vibroseis seismic surveys used to map the ice shelf cavity ...